FREQUENCY OF VERTEBRO-SPINAL ANOMALIES IN PATIENTS PRESENTING WITH ANORECTAL MALFORMATIONS. A DEVELOPING COUNTRY, SINGLE CENTRE STUDY (Journal of Medical & Health Sciences Review, 2025)
Background: To determine the frequency of different vertebro-spinal anomalies in patients with anorectal malformation presenting in developing country.Study Design: Prospective observational studyDuration of study: Duration of study is 6 months.Methods: After approval from the institutional review board, 106 pediatric patients after fulfilling selection criteria were enrolled in the study using non-probability convenience sampling technique. Informed consent was obtained from the guardian of patients. Baseline data of enrolled patients were recorded after careful history taking and examination. Subsequently, these patients underwent imaging through whole body X-rays and spinal cord MRI (Magnetic resonance imaging). Findings in the MRI were noted. The collected data was analyzed through SPSS v.26.Results: We enrolled 106 patients in current study with mean age was 4.48±2.84 years and birth weight was found 2.58±0.52 kg. Out of 106 enrolled patients 62(58.5%) were male and 44(41.5%) patients were female. The male to female ratio was 1.41:1 in current study. The frequency of vertebro-spinal anomalies were found in current study as: 8(7.5%) patients had sacral agenesis, 4(3.8%) patients had scoliosis, 6(5.7%) patients had tethered cord and 2(1.9%) patients had thickened filum terminale. Overall frequency was 18.9%.Conclusion: 18.9% of ARM (anorectal malformation) patients were found to have vertebro-spinal anomalies. Sacral agenesis was present in 7.5% of patients (n = 8) and Tethered cord was present in 5.7% of patients (n=6). The presence of VACTERL-association was shown to be associated to the presence of vertebrospinal anomalies. Therefore, we emphasize the importance of screening for vertebro-spinal anomalies in patients with ARM, regardless of ARM type.